Therapy for benign rectal anastomotic stricture after surgery for colorectal cancer: A systematic review - Gaoyang Cao; Songtao Wu; Li Zhang; Xinjie Zhang; Wei Zhou (Laparoscopic, Endoscopic and Robotic Surgery)
Objective: To evaluate various treatment methods for benign rectal anastomotic stricture (AS) following surgery for colorectal cancer. Method: A systematic review of the literature was conducted, focusing on studies that reported outcomes of different treatment modalities for benign AS. The PubMed, Embase, Scopus, China National Knowledge Infrastructure, and Cochrane Library databases were searched from January 2000 to December 2023. The inclusion criteria were studies involving human subjects, published in English, and reporting on therapeutic outcomes for benign AS. Results: A total of 19 papers identified a range of therapeutic strategies, including nonoperative anastomotic dilation, endoscopic balloon dilation (EBD), transanal minimally invasive surgery (TAMIS), self-expandable metal stents (SEMS), endoscopic incision (EI) and newer techniques such as prostate resection instrumentation. Nonoperative anastomotic dilation can serve as an initial treatment for lower AS. EI demonstrated promise in cases where EBD was ineffective, providing an alternative method for managing AS. TAMIS and SEMS showed higher efficacy in refractory cases, with TAMIS being particularly effective for severe fibrotic or completely closed AS. The use of rigid instrumentation with an electric knife for transanal incisions demonstrated precision but lacked the flexibility needed for complex procedures. Conclusion: While traditional methods such as nonoperative anastomotic dilation and EBD remain first-line treatments for benign AS, advanced techniques such as EI, TAMIS, and SEMS offer promising alternatives, particularly in refractory cases. The choice of treatment should be tailored to individual patient conditions, with consideration for the technical expertise required and the potential for complications.